Phytophthora Crown Rot of Strawberry - Natalia A Peres; Juliana S. Baggio (EDIS, 2019)
This new 3-page article describes Phytophthora crown rot, an important disease in Florida strawberry fields caused mainly by Phytophthora cactorum, and provides some recommendations for cultural and chemical control. Written by Natalia A. Peres and Juliana S. Baggio and published by the UF/IFAS Plant Pathology Department. https://edis.ifas.ufl.edu/pp350